Nitric Oxide as a Beneficial Signaling Molecule in Trichoderma atroviride TRS25-Induced Systemic Defense Responses of Cucumber Plants Against Rhizoctonia solani - Nawrocka, Justyna; Gromek, Aleksandra; Małolepsza, Urszula (Frontiers in Plant Science, 2019)
In the present study, T. atroviride TRS25 is presented as a biological control agent which significantly limits the development of infection and reduces the disease caused by the pathogenic fungus R. solani in cucumber plants (C. sativus L.). The systemic disease suppression is related to oxidative, signaling and biochemical changes which may trigger cucumber defensive reactions to the pathogen. Induction of systemic defence in cucumber by TRS25 greatly depends on the accumulation of signaling molecules including hydrogen peroxide (H2O2) and nitric oxide (NO) as well as salicylic acid (SA) and its derivatives including methyl salicylate (MeSA) and octyl salicylate (OSA). The study established that NO was accumulated in leaves and shoots of the cucumber plants, especially those pretreated witch Trichoderma and inoculated with R. solani, where the compound was accumulated mainly in the cells localized in the vascular bundles and in dermal tissues. We suggest, for the first time, that in the plants pretreated with TRS25 the accumulation of H2O2 and NO may be related to catalase (CAT) and S-nitrosoglutathione reductase (GSNOR) activity decrease. On the other hand, excessive accumulation of NO and SA may be controlled by forming their inactive forms, S-nitrosothiols (SNO) and salicylic acid glucosylated conjugates (SAGC), respectively. The obtained results suggest that the mentioned molecules may be an important components of the complex signaling network activated by TRS25, which is positively involved in systemic defence responses of cucumber plants against R. solani.